Association of interleukin 4 and MTHFR gene polymorphisms with distal symmetrical polyneuropathy in young diabetics - Raquel Garcia Rocco da Silva; Marcelo A. Costa Lima; Claudia de Melo Moura; Jorge Luiz Luescher; Ludmila Nascimento Rodrigues Campos; Daniel de Souza e Silva; Márcia Gonçalves Ribeiro (Arquivos de Neuro-Psiquiatria)
Background It is believed that genetic factors play a role in the development and severity of neural injury among people with distal symmetrical polyneuropathy (DSP), because some genes are involved in specific biological pathways, acting in different ways in the pathogenic process.